2018
DOI: 10.1016/j.molp.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

VERNALIZATION1 Modulates Root System Architecture in Wheat and Barley

Abstract: Roots play a key role in plant growth regulation. It is well described that the below-ground plant architecture has a significant impact on plant performance under abiotic constraints and maintains stability under increased grain load (Lynch, 2013). Although loci influencing root traits have been shown to affect grain yield and agronomic performance (e.g., Canè et al., 2014), knowledge about the genetic control of root growth in major grain crops is limited. Here, we demonstrate that VERNALIZATION1 (VRN1), a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 11 publications
5
91
0
2
Order By: Relevance
“…Still, it was already demonstrated that the presence of the gene DEEPER ROOTING 1 (DRO1) in rice cultivars affords the crop yield stability under drought, and it does not cause any penalty under irrigated conditions (Uga et al, 2011(Uga et al, , 2013. This finding is also in agreement with Voss-Fels et al (2017), who found that VERNALIZATION 1, a key gene influencing flowering time and aboveground development in wheat, also has an important pleiotropic role on root system architecture and alone controls 8% of RA total variation.…”
Section: Field Variation For Grain Size Based On Differences In Root supporting
confidence: 69%
See 1 more Smart Citation
“…Still, it was already demonstrated that the presence of the gene DEEPER ROOTING 1 (DRO1) in rice cultivars affords the crop yield stability under drought, and it does not cause any penalty under irrigated conditions (Uga et al, 2011(Uga et al, , 2013. This finding is also in agreement with Voss-Fels et al (2017), who found that VERNALIZATION 1, a key gene influencing flowering time and aboveground development in wheat, also has an important pleiotropic role on root system architecture and alone controls 8% of RA total variation.…”
Section: Field Variation For Grain Size Based On Differences In Root supporting
confidence: 69%
“…As mentioned, extending water availability after anthesis is normally linked to a prolonged grain-filling period before drying out. This finding is also in agreement with Voss-Fels et al (2017), who found that VERNALIZATION 1, a key gene influencing flowering time and aboveground development in wheat, also has an important pleiotropic role on root system architecture and alone controls 8% of RA total variation. All traits connected to RA show very high heritability and were not affected by the simulated water scarcity after anthesis, which as indicated above, supports the case for strong genetic control.…”
Section: Field Variation For Grain Size Based On Differences In Root mentioning
confidence: 99%
“…Since modern varieties have been selected with limited or no knowledge of belowground interactions, how was the capacity of shaping the rhizosphere microbiota retained within the cultivated germplasm? The recent observation that genes controlling reproductive traits display pleiotropic effects on root system architecture 51 could provide a direct link between crop selection and microbiota recruitment in modern varieties. These traits, and in particular genes encoding flower developments, show a marked footprint of eco-geographic adaptation and have been selected during plant domestication and breeding 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Vigor, an elusive but important target in most crop breeding programs, is related to both nutrient capture and utilization. Phenology regulates the duration and extent of soil exploration, as well as the duration of nutrient utilization in plant tissue, and is therefore closely linked to nutrient efficiency (Nord & Lynch, ; Voss‐Fels et al ., ). Many of these are common selection criteria in crop breeding.…”
Section: Nutrient Targetsmentioning
confidence: 97%